A regularização fundiária de ocupações e o Código Civil - Pereira, André Laubenstein (2009)
This work analyzes the applicability of the article 1.228, §§4º and 5º of the brazilian Civil Code to the regularization of irregular land habitations (squats and slums), based both on the Tridimensional Theory of Law and the Theory of Legal Principles. To materialize that objective, the study evaluates, at a first moment, the evolution of the right of property (ownership) and of the possession, as well as its social functions in the current legal system in Brazil. As source of research, works of Brazilian authors and foreign jurists were consulted. After that, the work analyzes the situation of the housing (homelessness) in the country, bringing some information about the lack of habitations and the squats and slums in some cities of Brazil. Some sources of the research were governmental agencies e non-governmental entities connected to habitation. Authors with works in the area of regularization of slums had been also consulted. Demonstrating the gravity of the problem and, in parallel, the insufficiency of financial conditions and the inefficiency of the governmental actions, this study aims to express that the State´s omission generates legal effects in the civil relations between the citizens involved in land´s irregular habitation (proprietors/owners and disseisors/squatters/possessors). Based upon this, the work justifies the applicability of the Brazilian Civil Code to conduct such effects in those legal relations, to avoid, not only a deficient State, but a defective legal system, capable to allow both acts of civil disobedience and perpetuation of innumerable injuries of rights. On this topic, the dissertation (master´s thesis) was based on the doctrine of the Constitutional Civil law. With the support on those premises, this thesis proposes a socially useful and innovative interpretation of the article 1.228, §§4º and 5º of the Brazilian Civil Code, which propagates a new form of eminent domain (condemnation or taking with the just compensation), with aptitude to supply an existing gap in the legal system. Such article is capable, in our point of view, to solve situations of old slums and squats (land´s irregular habitation), in which, on one hand, the owners are not capable to get back their possession, neither obtain any type of compensation for the loss of the land, and, on the other hand, the possessors also are unable to legalize their possession and housing